Single Shareholder Company in Africa, America and Australia: A Comparative Analysis - Salah Mohammed Almasabi; Hazlina Shaik MD Noor Alam; Hasai Mohd Ali (Faculty of Law, Sriwijaya University, Indonesia, 2023)
Single Person Companies (SPCs), known as One-Person Companies (OPCs), are a revolutionary concept and a new invention in the field of international company law. This study aims to investigate the meaning of OPC and how it is used in three different continents, namely Africa, America, and Australia, focusing on legal entity, OPC incorporation process, minimum share capital, nominee appointment, and OPC conversion. The researchers used the doctrinal data collection method to study relevant journals, articles, books, papers, and internet sources. When choosing the sample States, the researchers use the Gross Domestic Products (GDPs) as a methodological yardstick. According to the findings, only a natural person may form an OPC in some jurisdictions, such as Caledonia and New Zealand. The ability of both natural and legal persons to incorporate OPC has been made explicit in nations including South Africa, Nigeria, Algeria, and Argentina. The outcome further illustrates that in nations like the USA and Caledonia, only citizens of such nations or individuals who are residents of New Zealand are eligible to incorporate OPC. The minimum share capital for creating an OPC should be reasonable to enable the lower class to establish OPC and fully control the business.